Optimising Fraction Operation Skills with Shaded Level Board for Elementary School Students (Project Based Learning, Course Review Horay and Teams Games Tournament) - Apriliyani, Putri; Darmiyati, Darmiyati (STKIP Singkawang, 2024)
One of the problems in this study is the low active participation of students in learning activities, low student creativity, and low student understanding of mathematics concepts, which results in poor learning outcomes. As a result of these problems, students experienced a decline in activity, creativity, and overall learning outcomes. This study aims to evaluate students' activity, creativity and learning achievement in grade V of SDN Pelambuan 1 Banjarmasin. The study also shows how the teacher handles the multiplication and division of fractions material. This study used the classroom action research or PTK method with qualitative and quantitative approaches for data collection and data analysis. In the 2023/2024 academic year, 28 Class V students. Quantitative data came from written exams conducted by students and teacher activities during class. The results showed that the project-based learning model, Horay Course Review, and Teams Games Tournament were acceptable. Teacher activity at the last meeting reached the